PENGARUH BAURAN PROMOSI DAN POTONGAN HARGA TERHADAP KEPUTUSAN PEMBELIAN SEPEDA MOTOR VARIO PADA PT. INDAKO TRADING COY HONDA LABUHANBATU UTARA - Jaya, Ridho Pratama; Othman, Lie (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2025)
This study aims to analyze the relationship and influence of promotional mix variables and discounts on purchasing decisions for Vario motorcycles at PT. Indako Trading Coy Honda Labuhanbatu Utara. The research method used in this study is quantitative. The data source in the study uses primary data and secondary data. The method of collecting sample data for this study was by distributing questionnaires and interviews by interviewing 99 respondents from 131 populations who purchased Vario motorcycles at PT. Indako Trading Coy Honda Labuhanbatu Utara. Based on the results of partial testing, it shows the influence of promotional mix variables on purchasing decisions. In the F test, it shows a simultaneous relationship between variables X and Y because Fcount> Ftable. The R Square result is 0.753. At this value, it can be seen that 75.3% of promotional mix variables and discounts have a positive influence on purchasing decision variables, 24.7% are influenced by other variables. Promotional mix helps consumers in searching for information and fulfilling product expectations. Discounts can provide benefits and relief for consumers who want to buy motorbikes to increase purchasing decisions at PT. Indako Trading Coy Honda North Labuhanbatu. Keywords: Promotion Mix, Discount, Purchase Decision.